2001
DOI: 10.1067/mcp.2001.116794
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic efficacy of rectal versus oral acetaminophen in children after major craniofacial surgery

Abstract: These are the first data showing that the analgesic acetaminophen plasma concentration after major surgery in this age group does not always reach the 10 to 20 mg/L level. These data also show that, after a rectal loading dose of 40 mg/kg has been given during surgery, the best way of administering acetaminophen after craniofacial surgery is the rectal route.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 20 publications
2
41
0
1
Order By: Relevance
“…There was a divergence between the conclusions of the two RCTs found on the first comparison; one appointed an effective pain control and equivalence in regards to nauseas and vomits (rectal loading dose of 40 mg/kg followed by 30 mg/kg 8 hourly) [36], whereas the other one did not observe effective pain control (single prophylactic dose of 40 mg/kg) [37], emphasizing the fact that both analyzed palatoplasties. These results are in concordance with the standard clinical practice that states a postoperative rectal loading dose (30–40 mg/kg) followed by regular maintenance doses (20 mg/kg 6 hourly or 30 mg/kg 8 hourly) [6870]. Besides the difficulties associated with rectal administration (e.g., delayed and erratic absorption), an RCT done in patients undergoing craniosynostosis repair verified a higher efficacy than oral administration [68].…”
Section: Discussionsupporting
confidence: 83%
“…There was a divergence between the conclusions of the two RCTs found on the first comparison; one appointed an effective pain control and equivalence in regards to nauseas and vomits (rectal loading dose of 40 mg/kg followed by 30 mg/kg 8 hourly) [36], whereas the other one did not observe effective pain control (single prophylactic dose of 40 mg/kg) [37], emphasizing the fact that both analyzed palatoplasties. These results are in concordance with the standard clinical practice that states a postoperative rectal loading dose (30–40 mg/kg) followed by regular maintenance doses (20 mg/kg 6 hourly or 30 mg/kg 8 hourly) [6870]. Besides the difficulties associated with rectal administration (e.g., delayed and erratic absorption), an RCT done in patients undergoing craniosynostosis repair verified a higher efficacy than oral administration [68].…”
Section: Discussionsupporting
confidence: 83%
“…15 Moreover, some evidence revealed that antipyretic serum concentration of 15-20 µg/mL could not be achieved by rectal dose of 10-15 mg/kg and a rectal dose of 30-45 mg/kg was needed. [15][16][17][18][19] In some circumstances, rectal preparation is used, such as when the patient is vomiting or the physician or parents prefer the rectal route. 20 By a computer-generated random table, subjects were assigned to one of two groups.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of effect in neonates is difficult, and attempts to show concentrationresponse relations have been unfruitful, 12 as in the present study. Assessment tools may measure discomfort rather than pain, neonatal wind up may exist, pain is not constant, placebo effects contribute, and large interindividual variability has been reported for pharmacodynamic parameter estimates.…”
mentioning
confidence: 90%